Review: The role of multiple placental glucocorticoid receptor isoforms in adapting to the maternal environment and regulating fetal growth. (June 2017) - Clifton, V.L.; Cuffe, J.; Moritz, K.M.; Cole, T.J.; Fuller, P.J.; Lu, N.Z.; Kumar, S.; Chong, S.; Saif, Z.
Abstract: The physiological mechanisms that confer different outcomes in morbidity and mortality of the fetus exposed to stressful environments may be driven by significant differences in the expression and function of the placental glucocorticoid receptor (GR). The recent discovery that the placenta contains at least 8 different isoforms of the GR raises questions about the regulation and physiological relevance of the many GR variants expressed in the placenta. The current data also highlights that individual differences in glucocorticoid sensitivity, variations in the effect of different complications of pregnancy on birth outcomes and sex differences in the response to stress, may all be dependent on a specific GR isoform expression profile. This review will investigate the current state of knowledge of GR isoforms in the placenta and discuss the potential role of these multiple isoforms in regulating glucocorticoid sensitivity.